(3JYOO GdLQGFe hGdYbhHGJ ai GdfXGe GdbGfhfi GdeUQi (B/ s - (3eUWai YHO GdYXje MSfs; (3CMeO YhV HdGd s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2007)
(3JOhQ GdQSGdI Mhd JYOO GdLQGFe heGgjJg ai JMOjO eaghe GdLQjeI hGdebUhO HGdJYOO hGdJejR Hjf GdhMOI hGdJYOO hcPG JWhQ acQI GdJYOO hUhQ GdYbhO JYOO eGOi hJYOO eYfhi heGjejR GdJYOO Yf GdMGdGJ GdeTGHgIs
(3CWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdLfGFj (B2007.s
(3HHdjhLQGajG(B: (3UaMGJ (B162-164.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFj GdYGes; (3GdYbhHGJ GdLfGFjIs; (3GdLQGFes; (3GdbGfhf GdLfGFjs -- (3eUQs; (3GdfXGe GdbGfhfi GdeUQis; (3JYOO GdLQGFes; (3eaghe GdLQjeIs; (3JYOO GdLQGFes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs